Coreceptor usage of Chinese HIV-1 and impact of X4/DM transmission clusters among recently infected men who have sex with men. Issue 39 (September 2016) - Li, Xiaoshan; Zhu, Kexin; Li, Wei; Fang, Kun; Musa, Taha Hussein; Song, Yue; Du, Guoping; Gao, Rong; Guo, Yan; Yan, Wenjuan; Xuan, Yang; Zhong, Ping; et al.
Abstract : Abstract: To characterize the current frequency of HIV-1 coreceptor usage in China and assess the candidacy of CCR5 antagonists for treatment of HIV infections. In addition, we aimed to evaluate the potential of X4/DM virus transmission in recently infected men who have sex with men (MSM) individuals. Viral tropism testing was performed on samples from 399 MSM individuals and on 2408 available Chinese HIV-1 V3 sequences downloaded from the Los Alamos database using Geno2pheno and WebPSSM in combination. The transmission clusters were evaluated using pol sequences from 291 recently infected MSM with a maximum likelihood, maximum pairwise distance, and Bayesian inference. A higher prevalence of X4/DM viruses was observed in individuals infected with CRF01_AE strains than with subtype B (27.8% vs 12.2%, P  < 0.001) and CRF07_BC/CRF08_BC/C (27.8% vs 1.0%, P  < 0.001). Seven clusters containing only X4/DM viruses were detected in 40 transmission clusters. No significant difference in proportions between clustered X4/DM viruses and R5 viruses was found ( P = 0.683). The high proportion of CXCR4 usage for CRF01_AE strains may result in the loss of susceptibility to maraviroc since CRF01_AE has become the most prevalent strains in China. The high prevalence of X4/DM viruses among recently CRF01_AE-infected individuals may be attributed to the stochasticity of HIV transmission, which implied that the early viral tropism screening and treatment would be the key for controlling the epidemic of CRF01_AE strains in China. Abstract : Supplemental Digital Content is available in the text